Aktivitas Metabolit Sekunder Cendawan Endofit terhadap Colletotrichum acutatum pada Cabai Merah - Nur Alfi Saryanah; Suryo Wiyono; Dadang Dadang (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2019)
Activity of Fungal Endophyte Secondary Metabolites against Colletotrichum acutatum on Chili PepperColletotrichum acutatum is one of anthracnose causal agents on chili pepper that has been reported to be predominant species in a some regions of Java Island. Secondary metabolites of endophytic fungi have been reported to have a potency as antifungal agents against plant pathogen. However, its antifungal activity against C. acutatum has not been reported yet. This study was aimed to evaluate the antifungal activity of fungal endophyte secondary metabolite against C. acutatum at in vitro and in vivo assay. In vitro assay was conducted to evaluate antifungal activity of fungal endophyte CBR1D14 isolate culture filtrate (FCBR) and mycelia extract (MCBR) in inhibiting conidial germination of C. acutatum. The results of in vitro assay showed that ethyl acetate extract of FCBR (EA FCBR) had the highest activity in inhibiting C. acutatum conidial germination. Methanol fraction from the partition of EA FCBR (FM FCBR) and from the partition of MCBR ethyl acetate extract (FM MCBR) showed the ability in inhibiting C. acutatum conidial germination. In vivo assay to chili pepper fruit showed that the treatment of FM FCBR (IC95 609.9 µg mL-1) and FM MCBR (IC95 1178.27 µg mL-1) decreased anthracnose disease incidence and lesion diameter. The efficacy rate of FM FCBR and FM MCBR treatments against anthracnose was 36.72 and 48.68%, respectively. Bioautography test was done on silica gel thin layer chromatogram. Methanol fraction of FCBR and MCBR were separated into 3 bioautographic spots respectively (Rf 0.04, 0.07, 0.7 for FM FCBR and Rf 0.06, 0.52, 0.7 for FM MCBR).